Proceedings of 14th VLSI Test Symposium
DOI: 10.1109/vtest.1996.510876
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of very-low-voltage testing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 13 publications
3
30
0
Order By: Relevance
“…Figure 3 shows that the changing rate of the propagation delay remains almost unchanged when the supply voltage is higher than 4V t . It starts increasing significantly when the supply voltage is reduced to about 2V t to 2.5V t , which is the same as the voltage range for VLV testing suggested in [2]. Tables 3 and 4 list the delay ratios between WD and fault-free gates at different voltages for the 0.8 µm and 0.6 µm technologies.…”
Section: Voltage Dependence Of Cmosmentioning
confidence: 65%
See 4 more Smart Citations
“…Figure 3 shows that the changing rate of the propagation delay remains almost unchanged when the supply voltage is higher than 4V t . It starts increasing significantly when the supply voltage is reduced to about 2V t to 2.5V t , which is the same as the voltage range for VLV testing suggested in [2]. Tables 3 and 4 list the delay ratios between WD and fault-free gates at different voltages for the 0.8 µm and 0.6 µm technologies.…”
Section: Voltage Dependence Of Cmosmentioning
confidence: 65%
“…Also, Hao and McCluskey have shown that VLV testing is effective in detecting threshold voltage shifts [1]. We will verify the supply voltage for VLV testing proposed in [2] is valid for detecting these timing failures too.…”
Section: Delay Flawsmentioning
confidence: 80%
See 3 more Smart Citations